The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/modl.12758
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversification and Progressive Routinization of a Multiword Expression in and for Social Interaction: A Longitudinal L2 Study

Abstract: In this article, we bring together conversation analysis and usage-based linguistics to investigate the second language (L2) developmental trajectory of a linguistic construction within the complex multimodal ecology of naturally occurring social interaction. We document how, over the course of 15 months, an L2 speaker's use of the French multiword expression comment on dit [how do you say] diversifies in both form and function. Two types of longitudinal change are observed: (a) The expression expands in its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…The studies reported here—in particular, those by Theodórsdóttir & Eskildsen (2022, this issue), Hellermann & Thorne (2022, this issue), and Pekarek Doehler & Skogmyr Marian (2022, this issue)—align with earlier work that stresses the value of rewilding language education (Thorne et al., 2021) in the form of pedagogical frameworks and infrastructures that center on L2 learners’ needs and experiences of language use outside the classroom. This addresses “the challenge of how to dynamically integrate formal learning settings with the vibrancy and diversity of linguistic, experiential, and situational contexts out in the world” (Hellermann & Thorne, 2022, this issue, p. 93).…”
Section: Implications For Language Educationsupporting
confidence: 80%
See 3 more Smart Citations
“…The studies reported here—in particular, those by Theodórsdóttir & Eskildsen (2022, this issue), Hellermann & Thorne (2022, this issue), and Pekarek Doehler & Skogmyr Marian (2022, this issue)—align with earlier work that stresses the value of rewilding language education (Thorne et al., 2021) in the form of pedagogical frameworks and infrastructures that center on L2 learners’ needs and experiences of language use outside the classroom. This addresses “the challenge of how to dynamically integrate formal learning settings with the vibrancy and diversity of linguistic, experiential, and situational contexts out in the world” (Hellermann & Thorne, 2022, this issue, p. 93).…”
Section: Implications For Language Educationsupporting
confidence: 80%
“…Second, similarly to Theodórsdóttir and Eskildsen's work, they point to the importance of examining how L2 usage patterns adjust to and develop in response to local interactional needs. This lends support to the argument that “grammatical routines may be motivated by social‐interactional exigencies” (Pekarek Doehler & Skogmyr Marian, 2022, this issue, p. 40; see also Couper–Kuhlen, 2011; Pekarek Doehler & Balaman, 2021). Importantly, the detailed qualitative analysis of the data reveals that the different uses of the multiword expression intertwine with precise embodied displays—in particular, recurrent gaze patterns.…”
Section: Respecifiying L2 Grammarsupporting
confidence: 58%
See 2 more Smart Citations
“…It depended on CA researchers adopting a more diachronic approach to investigate the learning of social practices (Hall, 2004; Larsen–Freeman, 2004). In their present contribution to this special issue, it seems to me that Pekarek Doehler and Skogmyr Marian (2022, this issue) have met this challenge. An important decision they made was to have the focus of their research emerge from the data, not from a preordained linguistic category.…”
Section: Discussion Of the Articlesmentioning
confidence: 96%